Depletion of CD4+ CD25+ regulatory T cells confers susceptibility to experimental autoimmune encephalomyelitis (EAE) in GM‐CSF‐deficient Csf2−/− mice. Issue 4 (2nd June 2016) - Ghosh, Debjani; Curtis, Alan D.; Wilkinson, Daniel S.; Mannie, Mark D.
Abstract : GM‐CSF controls the functional balance of effector and regulatory T cell subsets in EAE. Abstract : Previous studies established that GM‐CSF‐deficient ( Csf2 ‐deficient) mice exhibit profound resistance to experimental autoimmune encephalomyelitis. This study addressed whether the resistance of Csf2 ‐deficient mice was a result of a requirement for GM‐CSF in controlling the functional balance between effector and regulatory T cell subsets during experimental autoimmune encephalomyelitis. The main observation was that treatment with the anti‐CD25 mAb PC61 rendered Csf2 ‐deficient mice fully susceptible to severe, chronic experimental autoimmune encephalomyelitis, with disease incidences and severities equivalent to that of C57BL/6 mice. When both donors and recipients were treated with PC61 in a passive model of experimental autoimmune encephalomyelitis, adoptive transfer of myelin‐specific Csf2 ‐deficient T cells into Csf2 ‐deficient recipients resulted in a nonresolving chronic course of severe paralytic experimental autoimmune encephalomyelitis. The peripheral Csf2 ‐deficient T cell repertoire was marked by elevated CD3 + T cell frequencies that reflected substantial accumulations of naïve CD44 null‐low CD4 + and CD8 + T cells but essentially normal frequencies of CD4 + CD25 + forkhead box P3 + T cells among the CD3 + T cell pool. These findings suggested that Csf2 ‐deficient mice had secondary deficiencies in peripheral T cell sensitization to environmental antigens. In accordance, myelin oligodendrocyte glycoprotein 35–55/CFA‐sensitized Csf2 ‐deficient mice exhibited deficient peripheral sensitization to myelin oligodendrocyte glycoprotein, whereas pretreatment of Csf2 ‐deficient mice with PC61 enabled the robust induction of myelin oligodendrocyte glycoprotein‐specific T cell responses in the draining lymphatics. In conclusion, the experimental autoimmune encephalomyelitis resistance of Csf2 ‐deficient mice, at least in part, reflects a deficient induction of effector T cell function that cannot surmount normal regulatory T cell barriers. Experimental autoimmune encephalomyelitis effector responses, however, are unleashed upon depletion of regulatory CD25 + T cells.